Sport specific fitness testing of elite badminton players - Chin, M. K.; Wong, A. S.; So, R. C.; Siu, O. T.; Steininger, K.; Lo, D. T. (British Journal of Sports Medicine, 1995)
There is a scarcity of descriptive data on the performance capacity of elite badminton players, whose fitness requirements are quite specific. The purpose of this paper is to investigate the physiological response of elite badminton players in a sport-specific fitness test. Twelve Hong Kong national badminton team players performed a field test on a badminton court. Six light bulbs were connected to a programming device causing individual bulbs to light up in a given sequence. The players were instructed to react to the flashes by running towards them, and striking shuttles mounted in the vicinity of the bulbs. Exercise intensity was controlled by altering the interval between successive lightings. A low correlation (r = 0.65) was found between the results of the field test and the rank-order list of subjects, based on an objective on-field physiological assessment and subjective ranking. This may be explained by the requirements of other factors besides physical fitness which contribute to success in elite level badminton competition. These factors may include, for example, technical skill, mental power, and aesthetic judgements on the court. Maximum mean (s.d.) heart rate data (187(8) beats.min-1) and blood lactate values (10.4(2.9) mmol.l-1) in this study showed that players were under maximal load during the field test. From the testing data, it seems reasonable to speculate that the intensity of level 3 (20 light pulses.min-1; 3.0 s.pulse-1) and level 4 (22 light pulses.min-1; 2.7 s.pulse-1) simulates the requirement of actual games energy expenditure of the Hong Kong badminton players exercising at close to their anaerobic threshold. The results also show that an estimate of fitness can be derived from measurements involving exercise closely resembling that which is specific for the sports activity in question. Improved training advice and guidance may result from such studies.